Microscale patterning of electrochromic polymer films via soft lithography - Jung, Jae Yeong; Joo, Seokwon; Kim, Da Seul; Kim, Kyoung Hwan; Shim, Tae Soup; Seo, Soonmin; Kim, Ju Hyung (International Journal of Polymer Science, 2018)
We present a direct fabrication technique of patterned polymeric electrochromic (EC) devices via soft lithography, enabling both negative patterning and positive patterning of the polymer. For this work, elastomeric polydimethylsiloxane (PDMS) molds were employed as not only stamps for direct contact printing of polymer inks but also templates for dewetting of polymer solutions under mild experimental conditions. We performed both negative patterning and positive patterning of a prototypical EC polymer and investigated the EC device characteristics according to solvents, solution concentrations, and pattern types. Eventually, the complex patterns, which cannot be realized by conventional shadow masking processes, and large-area structures were successfully demonstrated. We anticipate that these results will be applied to the development of various patterned devices and circuits, which may lead to further applications.
Keywords: Device characteristics; Direct fabrications; Electrochromic polymers; Experimental conditions; Microscale patterning; Polydimethylsiloxane PDMS; Soft lithography; Solution concentration